How and why fathers are involved in their children's education: gendered model of parent involvement. Issue 3 (27th May 2018) - Kim, Sung won
Abstract: Accumulating evidence points to the unique contributions fathers make to their children's academic outcomes. However, the large body of multi-disciplinary literature on fatherhood does not address how fathers engage in specific practices relevant to education, while the educational research in the United States focused on parent involvement often excludes fathers. There is no theoretical framework up to date explaining the gendered nature of parental educational involvement. How and why might fathers' involvement differentially influence children's achievement from mothers'? In this article, based on a review of existing research locating school involvement as a major area of difference between fathers and mothers, I propose a revised model describing the sources of father involvement drawing on Hoover-Dempsey and Lamb's models of parent involvement and fathering explaining why fathers and mothers might differ over school involvement.